The essence and the concept of separation (redistribution) of land as a socio-economic categories and functions of state land policy implementation - Lobunko, A. (Land Management, Cadastre and Land Monitoring, 2017)
The problem of separation (division) of land is one of the traditionally complex and, so far, unsolved problems. First, the problem of separation (division) of land in terms of the scientific approach should be solved using the methods of discrete mathematics, cluster analysis methods, theory-busting and other methods of mathematical statistics. Second, approaches to separation (division) of land associated with the peculiarities of the functions that the earth takes in society, the selected criteria for the classification of land, which in turn can not be absolute and uniform for all occasions. Such an approach is not possible even in theory. The division (split) of land should be based on clearly defined target criteria, parameters and characteristics, the system is determined by the specific subject area and the requirements of specific user groups. In this regard, the study of nature and the concept of separation (redistribution) of land as an economic category and function realization of the state policy on land use and protection are closely related to the scientific substantiation of distribution of land on the main intended purpose, taking into account the state, public and private interests. However, the division (redistribution) of land depends on the needs and interests of land rights, including location (land area) accommodation, food security and restore physical strength and spiritual needs. Depending on the needs and interests of the people (society) and should be distribution (redistribution) of land. The study developed logical-semantic diagram essence division (distribution) of land, which is to select the most effective use and protection taking into account the value of natural resources and suitability of land for appropriate purposes, which aims to meet the land needs and interests of citizens, legal entities, local communities and the state in the land. Accordingly, in the division (distribution) of land is the process of land distribution, taking into account the value of natural resources and suitability of land for appropriate purposes, which aims to meet the land needs and interests of citizens, legal entities, local communities and the state in the land. Implementation of evidence-based separation (division) of land in their categories, types of land use purpose and lands is one of the functions of the state to implement the land policy. Keywords: division of lands into categories, types of purpose, classification of lands.